The art of tentativity: delivering interpretations in psychodynamic psychotherapy - Stukenbrock, Anja; Deppermann, Arnulf; Scheidt, Carl Eduard (Journal of pragmatics, 2021)
In psychotherapy, therapists often formulate interpretations of clients' prior talk which are ‘unilateral’ in the sense that therapists index that they are themselves the author of an interpretive inference which may not be acceptable to the client. Based on 100 German-language recordings of brief psychodynamic psychotherapy (4 clients with 25 sessions each), we describe a multimodal practice of constructing extended multi-unit turns of delivering therapeutic interpretations. The practice includes gaze aversion until the main point of the interpretation is reached, perceptive and cognitive formulae, epistemic hedges, inserted accounts, parenthesis, self-repair, and self-reformulations. These design-features work together to index that the therapist produces an interpretation that can be heard as being tentative. The design of the therapists' turns reflexively indexes the expectation that the client might resist the interpretation; at the same time they are constructed to avoid resistance and to invite the client's self-exploration into new directions, often with a focus on emotions.